2021
DOI: 10.3390/ijerph18115592
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review about Imaging and Histopathological Findings for Detecting and Evaluating Electroporation Based Treatments Response

Abstract: Background: Imaging methods and the most appropriate criteria to be used for detecting and evaluating response to oncological treatments depend on the pathology and anatomical site to be treated and on the treatment to be performed. This document provides a general overview of the main imaging and histopathological findings of electroporation-based treatments (Electrochemotherapy—ECT and Irreversible electroporation—IRE) compared to thermal approach, such as radiofrequency ablation (RFA), in deep-seated cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 108 publications
0
19
0
Order By: Relevance
“…Therefore, in contrast to what was reported Dr Kozak and colleagues [1], IRE cannot be defined with the term of ECT, and, although both IRE and ECT can be safely used to treat LAPC patients, these techniques are profoundly different [6][7][8][9][10]. Some authors have evaluated the feasibility and effectiveness of electrochemotherapy on deep tumours [6][7][8][9][10][11][12][13][14][15][16][17][18]. In our previous study we showed that electrochemotherapy on pancreatic tumours can be performed safely and feasibly [6].…”
Section: Dear Editormentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, in contrast to what was reported Dr Kozak and colleagues [1], IRE cannot be defined with the term of ECT, and, although both IRE and ECT can be safely used to treat LAPC patients, these techniques are profoundly different [6][7][8][9][10]. Some authors have evaluated the feasibility and effectiveness of electrochemotherapy on deep tumours [6][7][8][9][10][11][12][13][14][15][16][17][18]. In our previous study we showed that electrochemotherapy on pancreatic tumours can be performed safely and feasibly [6].…”
Section: Dear Editormentioning
confidence: 98%
“…In conclusion, we believe that the readers of "Polish Journal of Radiology" should know that the term IRE should not be confused with the term electrochemotherapy, which is reserved for a combination of low doses of chemotherapeutic drugs with an electrical field that determines a transient increase of cell permeability (reversible electroporation) [13][14][15][16][17][18].…”
Section: Dear Editormentioning
confidence: 99%
“…In contrast to RFA and MWA, IRE and ECT [ 21 , 23 , 39 , 40 ] are non-thermal techniques that cause ablation by changing cell membrane permeability using an induced electric field (electroporation). IRE is considered a direct ablation tool, since electroporation is used in an irreversible manner, causing the irreversible permeabilization of the lipid bilayer, the disruption of cellular homeostasis and stimulation of apoptotic pathways, causing death of neoplastic cells.…”
Section: Rfa Mwa and Other Treatmentsmentioning
confidence: 99%
“…One of the major fields of application of ablation treatment is liver tumors [ 21 , 22 , 23 , 24 ], with hepatocellular carcinoma (HCC) and metastases representing the principal targets [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. With respect to HCC, ablation treatments are considered as upfront treatments in patients with early-stage disease [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high mortality rate is correlated with several factors, of which the main is the late disease stage at which the majority of patients are diagnosed [14][15][16][17][18][19][20][21][22][23][24][25][26]. In fact, pancreatic cancer is asymptomatic until the disease develops to an advanced stage, and at diagnosis only about 20% of cases are eligible for surgical resection [27][28][29][30][31][32]. In addition, even after the surgical approach, the majority of patients will experience a recurrence, with five-year survival only up to 25% [3,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%